Diseño e implementación de un sistema electrónico para la medición y registro de velocidad de un vehículo mediante GPS. - Zambrano Vera, Roberto Gregorio (2019)
The following work focuses on the design and implementation of a device; using as a main technology the Global Positioning System (GPS, Global Positioning System) to give information on the speed, position and date, acquired during the journey of a vehicle, and then send this information to a database through the Global System for Mobile Communications (GSM, Global System for Mobile Communications), this information could be used as evidence for a possible fine that has been raised in error. For the development of this device, a peripheral interface controller (PIC, Peripheral Interface Controller), a GPS module and a GSM/GPRS module were used. Its operation is based on the triangulation and measurement of the delay signal that occurs when communicating between the receiver and the GPS satellite In addition, the system generates a database in which the speed, position and time information is saved. Every five seconds the information is updated and sent by means of a GSM/ GPRS module at the end of the tour. The objective is to use that information as evidence to appeal a possible photomult or use the information for particular activities. The system also seeks future integration into a broader system that allows sharing this information to a database that contains data from several registered vehicles.